The effects of needle and warm needle on hemodynamic responses at different acupoints in patients with knee osteoarthritis - Ni, Ahui; Chen, Qianqian; Huang, Jiayi; Liu, Caiyu; Zhu, Jiayi; Yu, Yating; Wang, Xiaoling; Jan, Yih-Kuen (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundAcupuncture, as a non-pharmacological alternative therapy, has been widely used in China for the clinical treatment of knee osteoarthritis (KOA). Different acupuncture methods and acupoint selections are two critical factors influencing clinical efficacy. Although multiple studies have confirmed the efficacy of acupuncture in treating KOA, its underlying physiological mechanisms remain unclear.ObjectiveThis study aimed to explore hemodynamic responses in KOA patients before and after interventions with different acupuncture methods and acupoint combinations, monitoring hemodynamic changes during acupuncture using near-infrared spectroscopy (NIRS).MethodsA total of 24 KOA patients received needle and warm needle interventions at SP10 (xuehai) and ST34 (liangqiu). NIRS was used to monitor real-time changes in oxygenated hemoglobin (HbO2), deoxy-hemoglobin (Hb), total hemoglobin (tHb), and oxygenation during acupuncture.ResultsCompared with needle, warm needle significantly increased HbO2 (P < 0.05) and oxygenation levels in KOA patients (P < 0.01). Both methods reduced Hb concentrations compared to baseline, with a greater decrease at ST34 than at SP10 (P < 0.05). However, during treatment, the warm needle showed an increase in the Hb concentration, especially in SP10.ConclusionOur study provides the first evidence that different combinations of acupuncture methods and acupoint selections can significantly affect hemodynamic responses. Warm needle significantly improved local blood flow and oxygen delivery capacity in KOA patients, maintaining these improvements longer than needle intervention. Furthermore, warm needle at SP10 demonstrated superior efficacy in improving oxygen metabolism compared to ST34​.